Multiple Cranial Nerve Palsy (MCNP) in Cerebral Sinus Vein Thrombosis (CSVT) due to Bilateral Septic Cavernous Sinus Granulomatous Abscess and Multiple Sinusitis: A Case Report - M. Ikhlas Muttaqin Aditiarman; M. Sofyan Faridi; I Wayan Tunjung; Dhesty Fadhilah Faatin (Lombok Medical Journal, 2026)
Case reports about cavernous sinus venous thrombosis (CSVT) with ophtalmoplegia are relatively rare caused by a long-standing dental infection complicated by a history of long-term smoking, leading to granulomatous abscesses and multiple sinusitis. A 48-year-old man admitted to the Emergency Department presenting of an inability to lift his left eyelid and to move his eyeball in any direction for the past 3 days, the symptoms were experienced suddenly. Multiple cranial nerves palsy (MCNP) or ophtalmoplegia in CSVT is a neurological disorder involving more than two non-homologous cranial nerves simultaneously. CSVT in this case occurs as a result of inflammation in response to granulomatous abscess of the cavernous sinus and multiple sinusitis due to a longterm untreated history of dental infection with long history of smoking. Clinical accompanying was progressive headache, ophtalgia, ptosis and proptosis. This case report highlights the importance of neuroimaging examinations, particularly CT scans, MRI, and MRA of the head, as the primary standard for establishing a diagnosis of CSVT, thereby enabling appropriate evaluation therapy and substantially determining a favorable prognosis